Analisis Hubungan Kondisi Lingkungan Rumah Dan Perilaku Keluarga Dengan Kejadian Serangan Asma Anak Di Kota Semarang 2005 - Kurniawati, Ari Dwi; Rahmatullah, Pasiyan; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2006)
Background : Total asthma patient in Telogorejo Hospital in the year 2004 had increased 63.20% from year ago. While the number of child asthma in patient by the year of 2004 also had increased by 15.83%. United State Environmental Protection Agency (US EPA) stated that environmental can caused asthma attack. Indoor house environment can give contribution to factors that cause asthma more than outdoor environment. This research was conducted to know the relation of environmental condition in housing and family behavior with the incidence of child asthma attack. Methods : This study was an observational research with a cross sectional approaches. Total sample in this research were 50 respondents child who had asthma. The variable divided into dependent variable of environmental condition in housing and family behaviors. Independent variable were air humidity, lights intensity, household furniture facility which was potential as allergen sources, dust, ventilation window¸ family behavior of AC usage, volatile organic compound,, animal keeping, insecticide and family members who smoke cigarettes. The dependent variable was child asthma attack. Results : The Result of this study showed that air humidity (RP=2,588; 95% CI 1,069-6,267; p=0,02), dust (RP=1,889; 95% CI 1,049-3,400; p=0,048) and the use of air conditioner (RP=1,889; 95% CI 1,099-3,226; p=0,040) related to the child asthma attack. Multiple logistics regression analysis showed that AC (OR=5,100; 95% CI 1,107 – 23,489; p=0,037) and dust (OR = 6,360; 95% CI 1,435 – 28,192; p=0,015) were potential risk factors of child asthma attack. Conclusions:It was concluded that environmental house condition and family behavior related to child asthma attack. Keywords : Child asthma attack, environmental condition of housing, family behavior.